Femtosecond laser–assisted cataract surgery versus standard phacoemulsification cataract surgery: Study from the European Registry of Quality Outcomes for Cataract and Refractive Surgery. Issue 12 (December 2016) - Manning, Sonia; Barry, Peter; Henry, Ype; Rosen, Paul; Stenevi, Ulf; Young, David; Lundström, Mats
Abstract : Purpose : To compare the visual, refractive, and adverse outcomes of femtosecond laser–assisted cataract surgery and conventional phacoemulsification cataract surgery. Setting : Cataract surgery clinics in 9 European countries and Australia (femtosecond‐assisted) and 18 European countries and Australia (conventional). Design : Multicenter case‐control study. Methods : Eyes having femtosecond laser–assisted cataract surgery were matched to eyes from the European Registry of Quality Outcomes for Cataract and Refractive Surgery phacoemulsification cataract surgery database for preoperative corrected distance visual acuity (CDVA), age, and preoperative risk factors. Intraoperative and postoperative complications, postoperative CDVA, and refractive outcome were compared. The follow‐up was 7 to 60 days. Results : The study matched 2814 femtosecond‐assisted cases to 4987 conventional phacoemulsification cases. Femtosecond‐assisted surgery compared as follows to conventional phacoemulsification: posterior capsule complications, 0.7% versus 0.4%; postoperative logMAR CDVA, 0.05 (6/6 −3 ) versus 0.03 (6/6 −2 ); worse postoperative CDVA at follow‐up (by 5 letters or more), 1.0% versus 0.4%; CDVA 0.3 (6/12) or better, 96.3% versus 97.1%; absolute biometry prediction error, 0.43 diopter (D) versus 0.40 D; within ±0.5 D of target, 72% versus 74.3%; and postoperative complications, 3.4% versus 2.3%. Conclusions : Femtosecond laser–assisted cataract surgery did not yield better visual or refractive outcomes than conventional phacoemulsification cataract surgery. Intraoperative complications were similar and low in both groups. Postoperative complications were lower in conventional phacoemulsification cataract surgery. Financial Disclosure : None of the authors has a financial or proprietary interest in any material or method mentioned.